Pengaruh Pemberian Kapsul Jintan Hitam terhadap Kadar Kolesterol Ibu Rumah Tangga - Bela Novita Amaris Susanto; Nindita Clourisa Amaris Susanto (Jurnal Sehat Mandiri, 2023)
Along with increasing age, a person's health condition can decrease, thus making him susceptible to various kinds of degenerative diseases. One of the early metabolic syndromes for degenerative diseases is high cholesterol levels. Prevention can be done by consuming black cumin which has a lot of content and benefits. The purpose of this study was to determine the effect of consuming black cumin capsules on total cholesterol, low density lipoprotein, high density lipoprotein and triglyceride levels in housewives. Quasi experimental research with one group pre-test post-test approach. Samples were taken by purposive sampling technique, amounting to 20 housewives. The research was conducted from March to July 2022 in Tangerang City. Laboratory measurements were carried out before and after administration of black cumin capsules at a dose of 3x1 capsules per day. The data were analyzed using the paired sample t-test. The results showed that the p value for total cholesterol, low density lipoprotein, high density lipoprotein, and triglycerides was < 0.001 (p < 0.05). There is an effect of consuming black cumin capsules on decreasing total cholesterol, low density lipoprotein and triglyceride levels, and effect on increasing high density lipoprotein levels. It is hoped that black cumin capsules can be used as a companion or additional therapy in controlling cholesterol levels in the body.